Edukasi Pencegahan Stunting dan Manajemen Pola Asuh dalam Pemenuhan Nutrisi pada Balita Melalui Pendekatan Terapi Komplementer: Edukasi Pencegahan Stunting dan Manajemen Pola Asuh dalam Pemenuhan Nutrisi pada Balita Melalui Pendekatan Terapi Komplementer - Ni ketut Ayu Mirayanti; Komang Sukraandini; Putu Gede Subhaktiyasa; Ni Ketut Citrawati; Sang Ayu Ketut Candrawati (Yayasan Ahmad Mansyur Nasirah, 2022)
Stunting is a chronic nutritional problem in toddlers which is characterized by a shorter height compared to children their age. According to the Data and Information Center of the Indonesian Ministry of Health (2018), said that the incidence of short toddlers or commonly referred to as stunting is one of the nutritional problems experienced by toddlers in the world today. The Bali Provincial Government Health Office Profile report (2018) that the percentage of short toddlers is quite high compared to the percentage of underweight and underweight toddlers, with the highest percentage of short toddlers being in the Bangli Health Center area of 44% of toddlers whose height was measured. The purpose of community service is to increase the knowledge and skills of mothers with toddlers in Stunting Prevention and Parenting Management in fulfilling nutrition for toddlers through complementary therapeutic approaches in Banjar Tegal Linggah, Songan A Kintamani Bangli Village, the method used is to provide counseling, demonstration and screening. The results obtained are 65% of mothers with toddlers understand about Stunting Prevention and Parenting Management in fulfilling nutrition for toddlers. 98% of mothers with toddlers are able to do complementary therapy with acupressure or massage techniques to increase appetite in toddlers.